TUNED MASS DAMPER FOR BASE ISOLATED STRUCTURES (Sciences & Technologie. B, Sciences de l'ingénieur, 2014)
Under strong earthquakes base isolator system could be bring to critical conditions as large displacement. In this study a hybrid control system for controlling vibration against strong earthquakes is introduced. A tuned mass damper is mounted on base isolated structure.Simulation on MATLAB is carried out on six degrees of freedom base isolated structures with elastic behaviour.The proposed hybrid system is tested underEl Centro,Hachinohe,Kobeand Northridge earthquakes. Results are compared to the same structures equipped just with a base isolator system.Results show that a base isolation system and a tuned mass damper (hybrid system) is more effective than a base isolation system alone, in reducing base isolation displacement and acceleration.